Preventive antioxidant strategies to reduce the effects of phthalate exposure on reproductive health - Mega Obukohwo Oyovwi; Joy Oluwasemilore Oyelami; Kehinde Henrietta Babawale; Benneth Ben-Azu (Discover Environment)
Abstract Phthalates, synthetic chemicals widely used in consumer products, are a significant public health concern due to their widespread exposure and demonstrated reproductive toxicity. Characterized by their diester structure, phthalates are encountered through various sources, including food packaging, personal care items, and building materials. Their primary mechanisms of reproductive harm involve endocrine disruption and oxidative stress, leading to a range of adverse effects such as decreased fertility, hormonal imbalances, and developmental anomalies. This review focuses specifically on mitigating these reproductive health risks by integrating antioxidant strategies into public health policies. We conducted a systematic review of epidemiological studies, laboratory experiments, and clinical trials, analyzing the correlation between phthalate exposure and reproductive health, the efficacy of antioxidant interventions, and the potential for policy integration. Our review confirms a strong association between increased phthalate levels and adverse reproductive health impacts. Furthermore, the evidence suggests that certain antioxidants can provide a protective effect against phthalate-induced damage, indicating their potential as a public health intervention. Therefore, this review calls for immediate public health policy changes to prioritize phthalate mitigation through strategies including antioxidant supplementation, dietary recommendations, and public awareness campaigns. Future research should focus on long-term efficacy and population-based implementation of these strategies, aiming to reduce the substantial burden of phthalate-induced reproductive toxicity.